DENOTATIVE AND CONNOTATIVE MEANING IN VIRGIN VS. CHAD MEME IN KNOW YOUR MEME SITE - Komara, Azkal Azkia Ibnu (Sanata Dharma University, Yogyakarta, 2024)
This research aims to find out how hidden meanings are conveyed in memes and the type of meme studied is a meme with the Virgin vs. Chad template and other similar template memes namely Swole Doge vs. Cheems on the official meme site and Know Your Meme's official Instagram account. By using descriptive qualitative methods, this research aims to analyze the meaning of denotation and connotation attached to several data. Researchers found 10 memes that use the template Virgin vs. Chad and 10 memes that use the Swole Doge vs. Cheems. The results of the analysis show that the denotational meaning in these memes shows figures that have been arranged and edited as creatively as possible by the creator without describing any further meaning, just figures and text written without context, while the connotative meaning in these memes describe the hidden meanings of the meme, such as how the meme template functions, the role of the figures displayed, and the written text has an implied meaning, whether it is the opinion of the meme maker, public opinion, facts in the field, even there are exaggerated opinions and even false information.